Monte Carlo analysis for solar PV impact assessment in MV distribution networks - Dilini Almeida; Jagadeesh Pasupuleti; Shangari K. Raveendran; M. Reyasudin Basir Khan (Institute of Advanced Engineering and Science, 2021)
The rapid penetration of solar photovoltaic (PV) systems in distribution networks has imposed various implications on network operations. Therefore, it is imperative to consider the stochastic nature of PV generation and load demand to address the operational challenges in future PV-rich distribution networks. This paper proposes a Monte Carlo based probabilistic framework for assessing the impact of PV penetration on medium voltage (MV) distribution networks. The uncertainties associated with PV installation capacity and its location, as well as the time-varying nature of PV generation and load demand were considered for the implementation of the probabilistic framework. A case study was performed for a typical MV distribution network in Malaysia, demonstrating the effectiveness of Monte Carlo analysis in evaluating the potential PV impacts in the future. A total of 1000 Monte Carlo simulations were conducted to accurately identify the influence of PV penetration on voltage profiles and network losses. Besides, several key metrics were used to quantify the technical performance of the distribution network. The results revealed that the worst repercussion of high solar PV penetration on typical Malaysian MV distribution networks is the violation of the upper voltage statutory limit, which is likely to occur beyond 70% penetration level.